Digital transformation in the halal industry: A bibliometric analysis of global research - Dupi, Muhamad Dupi; Inayat, Inayat Ullah Baloch (International Journal of Halal Industry, 2025)
Purpose – This study explores the global literature trends concerning the digital transformation of the halal industry through the lens of a bibliometric methodology by finding key countries, institutions, journals, authors, thematic clusters, and co-occurring keywords and emphasizing the point of intersection of digitalization and sustainability as a potential future research direction. Methodology – Bibliometric analysis and visualization were used to conduct the research using the Scopus database and VOSviewer software. A total of 298 articles published between 2011 and 2025 were analyzed. Signs of publication increase, citation trends, country and institutional cooperation, and keyword co-occurrence networks were analyzed. Findings – It was discovered that the growth of publications has been rapid since 2018, peaking in 2024. Malaysia and Indonesia were the major contributors, and hence, the central role of Southeast Asia. Keywords were dominated by blockchain and halal, as research no longer focused on certification and food safety but on state-of-the-art technologies such as blockchain, AI, and machine learning. There was also the identification of strong institutional collaborations in the Journal of Islamic Marketing. Implications – This research offers lessons to policymakers, scholars, and the industry to improve halal practices using digital technologies with a focus on transparency, traceability, and sustainability in global supply chains and certification systems. Originality – This work provides a detailed bibliometric review of digital transformation in the halal sector and the concept of twin transformation, connecting digitalization with sustainability and resilience in the international halal ecosystem.